Device architecture optimization of solder ball joints fatigue lifetime under random vibration frequencies. Issue 1 (15th October 2020) - Gao, Yang; Wang, Fuwei; Ding, Shaohu; Yang, Bin; Liu, Lin; Salmani, Mohammad
Abstract : Purpose: This study aims to investigate the vibration effects on ball grid array lifetime. Design/methodology/approach: Several finite element method simulations and experiments were performed. Findings: An optimized circuit configuration was found. Originality/value: The originality of paper is confirmed by authors.